Public Services for Prisoners in Tondano Correctional Institution Class IIB - Marbun, Royanto Julius; Mandagi, Marthinus; Mokat, Jetty E. H. (Technium Social Sciences Journal, 2024)
This research aimed to 1) To find out whether health services for Prisoners (Indonesian: Warga Binaan Pemasyarakatan or WBP) at Tondano Correctional Institution Class IIB have been met according to basic health care service standards; 2) To find out whether health services for Prisoners at Tondano Correctional Institution Class IIB have been met according to basic standards of infrastructure, and; 3) To find out whether health services for Prisoners at Tondano Correctional Institution Class IIB have been met according to basic human resource standards; The research method used is a qualitative research method with purposive sampling technique. The results of the research show that 1) Basic health care service standards in Tondano Correctional Institution Class IIB, which are described in 13 basic health care standard parameters, have in principle been attempted to be implemented, but the facts described show that not all of them meet the standards; 2) The basic standards of facilities and infrastructure to support the implementation of health services as previously described have not been met ideally in accordance with the supposed needs; 3) Fulfillment of basic human resource standards to support health services in Tondano Correctional Institution Class IIB cannot be achieved due to limited human resources.